HEAVY METAL-INDUCED INHIBITION OF ENZYMATIC ACTIVITY IN HEN EGG WHITE LYSOZYME - Pazmiño, Michel; Monica, Silva; James, Welbaum; Juan, Gaibor; Jose Luis, Altuna; Wilman, Carrillo (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to determine the content of chromium (Cr), nickel (Ni), cadmium (Cd), boron (B), mercury (Hg), and lead (Pb) in chicken hen eggs in hen's eggs and to evaluate their influence on the enzymatic activity of hen egg white lysozyme (HEWL). Methods: In this study, we have determined the content of Cr, Ni, Cd, B, Hg, and Pb in chicken hen eggs using absorption atomic (AA) method. The residual enzymatic activity of HEWL, HEWL was evaluated using spectrophotometric method. Results: The levels of Cr, Ni, Cd, B, Hg, and Pb in hen eggs were 1.8300, 1.1300, 0.5350, 0.5200, 0.0025, and 0.0021 mg/kg, respectively. The inhibition of enzymatic activity of HEWL, by exposure to heavy metals was studied. We found that Cr, Ni, Cd, B, Hg, and Pb produced a loss of enzymatic activity. Cr III was the metal with the highest reduction of HEWL enzymatic activity. 0.01 M of Cr III was able to reduce HEWL enzymatic activity levels up to 49% after 24 h of exposure to this metal. An exposure of 0.05 M of Cr III reduced HEWL enzymatic activity to 1%. 24 h exposure to 0.01 M of Cd presented a reduction of 37% of HEWL enzymatic activity and 0.05 M of Cd resulted in only 75% of HEWL enzymatic residual activity. Conclusions: Content of heavy metals in hen egg from Tungurahua region was high. Cr, Ni, Cd, B, Hg, and Pb produced a loss of enzymatic activity of HEWL.